Birds control pod borers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
If farmers can attract insectivorous birds to their fields, yields are likely to rise by more than a third. Such birds can reduce damage by pests, such as pod borers, very effectively. These are the conclusions from recent trials in Bangalore,...